Facet joint injection versus epidural steroid injection for lumbar spinal stenosis: intra-individual study. Issue 1 (January 2017) - Shim, E.; Lee, J.W.; Lee, E.; Im, T.; Kang, Y.; Ahn, J.M.; Kang, H.S.
Abstract : Aim: To evaluate the efficacy of facet joint injection (FJI) for patients with lumbar central canal stenosis (LCS) in comparison with epidural steroid injection (ESI) in the same individuals. Material and methods: Two hundred and fifty-two patients who underwent both FJI and ESI for LCS between January 2014 and December 2014 were considered for enrolment in the study. A radiologist retrospectively conducted a chart review and recorded which injection was chosen as the third injection after sequential injections of FJI and ESI, and why clinicians chose the particular injection method. The response was measured via the use of a five-point satisfaction scale. Results: Among 252 patients, only 73 patients were included in the study (the remaining patients did not fulfil the inclusion criteria). Out of 73 patients (mean age, 69.7 years; range, 49∼87 years), 50 patients had received a third injection, 33 patients (66%) underwent FJIs as a third injection. Out of 19 patients who had experienced an ineffective first ESI, 13 (68.4%) patients reported the second FJI as effective. Out of six patients for whom the first FJI had been ineffective, three (50%) patients reported the second ESI as effective. Conclusion: FJIs can be administered as an alternative to ESIs in cases of LCS. Highlights: Epidural steroid injection (ESI) can rarely cause significant complications. Facet joint injection (FJI) showed effectiveness for lumbar radiculopathy in lumbar central canal stenosis. FJI can be an alternative option to ESIs in lumbar central canal stenosis.